ChemInform Abstract: Toward the Total Synthesis of Klaivanolide: Complete Reinterpretation of Its Originally Assigned Structure. Issue 14 (April 2015) - Ferrie, Laurent; Ferhi, Sabrina; Bernadat, Guillaume; Figadere, Bruno
Abstract: The originally proposed structure of klaivanolide, an antiparasitic natural product isolated from Uvaria klaineana, is revised based on both experimental evidence by attempted total synthesis as well as spectroscopic data.